Optimization : theory and practice - Beveridge, Gordon S. G.; Schechter, Robert Samuel (New York : McGraw-Hill, 1970)
It presents a broad but unified coverage of the fundamentals at an introductory level.
Includes index.
Includes bibliographical references: p. 735-756.
ucj 17/01/2019
Loans
Keywords: Mathematical optimization